2017
DOI: 10.1371/journal.pone.0178552
|View full text |Cite
|
Sign up to set email alerts
|

Non-standard radiotherapy fractionations delay the time to malignant transformation of low-grade gliomas

Abstract: Grade II gliomas are slowly growing primary brain tumors that affect mostly young patients. Cytotoxic therapies (radiotherapy and/or chemotherapy) are used initially only for patients having a bad prognosis. These therapies are planned following the “maximum dose in minimum time” principle, i. e. the same schedule used for high-grade brain tumors in spite of their very different behavior. These tumors transform after a variable time into high-grade gliomas, which significantly decreases the patient’s life expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…The model simulations showed that only a rather moderate increase of it can be achieved for the considered parameter values under the restriction of maximum treatment duration of 6 weeks. However, the results suggested that sufficient tumor growth delays might be obtained for much longer treatments of slowly-proliferating tumors, which is in agreement with other theoretical studies [59,60]. Moreover, the presented model did not account for the drainage of necrotic tissue, which should be crucial for such problem.…”
Section: Discussionsupporting
confidence: 84%
“…The model simulations showed that only a rather moderate increase of it can be achieved for the considered parameter values under the restriction of maximum treatment duration of 6 weeks. However, the results suggested that sufficient tumor growth delays might be obtained for much longer treatments of slowly-proliferating tumors, which is in agreement with other theoretical studies [59,60]. Moreover, the presented model did not account for the drainage of necrotic tissue, which should be crucial for such problem.…”
Section: Discussionsupporting
confidence: 84%
“…This result was later extended for different doses per fraction and time spacing between doses in Ref. [27]. Mazocco et al [31] found a similar result using in-silico simulations of the Ribba’s et al model [29].…”
Section: Discussionmentioning
confidence: 58%
“…Some previous models have explored different therapeutic regimens for low-grade gliomas [27, 28, 31, 34]. First, in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this model is that it contains a spatial structure and also allows a slow decrease in the tumor radius after the end of the RT treatment. The authors used the model to study the impact of a fractionation of the RT treatment [ 20 , 24 ]. However, these studies are theoretical, and the model was not applied to real clinical data.…”
Section: Introductionmentioning
confidence: 99%